2017
DOI: 10.1111/jtxs.12270
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oil and shortening in rice bread quality: Relationship between dough rheology and quality characteristics

Abstract: This study showed that the type and quantity of fat added in rice based breads affect the bread quality in a different way. In general, it can be said that the incorporation of up to 20% oil improved rice based breads. Oil increased the specific volume, the a* and b* parameters of the crust and the cell density. It also decreases hardness, cohesiveness, springiness, resilience, and the L* parameter. Converse to breads made with oil, the addition of shortening can negatively affect the quality of the breads. Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 26 publications
6
31
0
3
Order By: Relevance
“…Mancebo et al . () reported a significant correlation between weight loss and specific volume, as this will affect the surface area of evaporation. However, the EBRF bread owned a higher volume, and it has no negative effect for bake loss.…”
Section: Resultsmentioning
confidence: 99%
“…Mancebo et al . () reported a significant correlation between weight loss and specific volume, as this will affect the surface area of evaporation. However, the EBRF bread owned a higher volume, and it has no negative effect for bake loss.…”
Section: Resultsmentioning
confidence: 99%
“…Oil addition improves the shelf life of breads. Furthermore, a reduction in dough consistency, achieved with the incorporation of oils (rather than solid fats; Moreira, Chenlo, & Torres, 2012), tends to result in an increased bread volume (Mancebo, Martinez, Merino, de la Hera, & Gomez, 2017). This is also usually accompanied by a reduction in hardness.…”
Section: Ingredientsmentioning
confidence: 99%
“…Several studies have demonstrated that the amount of water used in the formulation of glutenfree breads significantly affects their specific volume and final characteristics (de la Hera et al 2013;McCarthy et al 2005;Ylimaki et al 1988). Thus, Mancebo et al (2017) observed that when greater amounts of water were included in the formulation, the specific volume of breads increased until achieving a maximum value for which the dough volume during fermentation or baking decreased. This effect was related to the influence of water on dough rheology, since a similar effect was observed when oil was added in doughs.…”
Section: Introductionmentioning
confidence: 99%